Dampak Manajemen Pendidikan Inklusi Yang Diberikan Pada Anak ABK - Harya Tamy Deby Ivancha; Islamiah Islamiah; Wendika Putra; Opi Andriani (Lembaga Pengembangan Kinerja Dosen, 2024)
The background to this research is that there are still many schools that have implemented inclusive education, but still provide general treatment or services to inclusive students. The aim of this research is to determine the management of inclusive education for Children with Special Needs (ABK). This type of research is qualitative research. Data sources were obtained from the school principal and four class teachers. The data in this research was obtained through documentation, observation and interviews. The research design used uses an indigenous psychology approach, part of the scientific approach tradition, where an important aspect in this approach is the effort to find appropriate methods to uncover phenomena in an investigation. The research results show that teachers directly handle the implementation of education. The treatment provided is good, such as providing special response and attention to children with special needs.